Agresi verbal pada anggota polri: Bagaimana peranan kohesivitas dan kematangan emosi? - dwi, gama; Amanda Pasca Rini; Sahat Saragih (INNER: Journal of Psychological Research, 2023)
This study aims to determine the relationship between cohesiveness, emotional maturity and verbal aggression among members of the Indonesian National Police. The participants in this study were 155 members of the Indonesian National Police who were taken using the simple random sampling Technique. The research instrument uses a cohesiveness scale, emotional maturity scale and verbal aggression scale. Based on the results of data analysis using multiple linear regression, the results obtained correlation coefficient = 0.373 with a significant level of p= 0.000, it is stated that there is a significant positive relationship between cohesiveness, emotional maturity and verbal aggression, the higher the cohesiveness and emotional maturity, the lower the verbal aggression on members of the Indonesian National Police and vice versa, the lower the cohesiveness and emotional maturity, the higher the verbal aggression towards members of the Indonesian National Police Keywords: Cohesiveness ; Emotional maturity ; Verbal Aggression